HUBUNGAN ANTARA TINDAKAN KELUARGA DAN PERAN JURU PEMANTAU JENTIK DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) PADA MASA PANDEMI COVID-19 DI KECAMATAN PANCORAN MAS, KOTA DEPOK, JAWA BARAT TAHUN 2021 - Savitri Hurriatul Maula (2022)
Dengue Hemorrhagic Fever (DHF) is one of the diseases that contributes to morbidity and mortality every year in Indonesia and still exists even though the world is being hit by the Covid 19 pandemic. There has been an increase in dengue cases from 2020 to 2021 in Depok City, even though currently it is still in a state of emergency. Pandemic and the implementation of Community Activity Restrictions. One of the efforts to reduce the number of dengue fever is the participation of families and local communities in preventing the onset of this disease. The purpose of this paper is to determine the relationship between family support and larva monitoring with the incidence of Dengue Hemorrhagic Fever (DHF) during the Covid 19 pandemic. The study used a cross sectional study design with Simple Random Sampling technique and the number of respondents was 121 people. Respondents filled out online questionnaires with the help of google forms. The bivariate analysis used resulted in a relationship between patient gender (0.041), patient mobility (0.042), family attitude (0.001), family action (0.000), and larva monitoring (0.033) on the incidence of DHF. Odds Ratio values in each variable are patient age (1.65), patient gender (3.01), patient mobility (3.62), family knowledge (3.07), family attitude (6.37), family action (31,28), and larva monitoring (3.31). It is recommended for families to take steps to prevent DHF because preventive measures affect the incidence of DHF.